2020
DOI: 10.21203/rs.3.rs-101027/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced eosinophilic inflammation associated with antibody and complement-mediated pneumonic insults in severe COVID-19

Abstract: Despite the worldwide effect of the Coronavirus disease 2019 (COVID-19) pandemic, the underlying mechanisms of fatal viral pneumonia remain elusive. Here, we conducted kinetic profiling of respiratory leukocytes and associated inflammatory mediators to show that severe COVID-19 is associated with delayed but enhanced eosinophilic inflammation when compared to mild cases. In addition, we confirmed increased Th2-biased adaptive immune responses, accompanying overt complement activation, in the severe group. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
0
1
Order By: Relevance
“…due to the presence of a crystalloid body containing cytotoxic proteins, such as eosinophil cationic protein (ECP) and eosinophil peroxidase, and eosinophil-derived neurotoxin (EDN) (Lindsley et al, 2020). In severe COVID-19, higher EDN and lesser ECP levels were reported in the younger patient than in elderly patients (Kim et al, 2021). In this study, cytolysis and release of the granules, apoptotic changes were observed.…”
Section: Eosinophilsmentioning
confidence: 65%
“…due to the presence of a crystalloid body containing cytotoxic proteins, such as eosinophil cationic protein (ECP) and eosinophil peroxidase, and eosinophil-derived neurotoxin (EDN) (Lindsley et al, 2020). In severe COVID-19, higher EDN and lesser ECP levels were reported in the younger patient than in elderly patients (Kim et al, 2021). In this study, cytolysis and release of the granules, apoptotic changes were observed.…”
Section: Eosinophilsmentioning
confidence: 65%
“…Η απομάκρυνσή της από τον ανθρώπινο οργανισμό είναι παρόμοια με της ενδογενούς ανοσοσφαιρίνης IgG. Πραγματοποιείται μέσω ενός αργού πρωτεολυτικού καταβο-1154GG και VEGF-634CC σχετίζονται με μεγαλύτερη παραγωγή VEGF έναντι των υπολοίπων γονοτύπων για τους VEGF-2578C/A, VEGF-1154G/A και VEGF-634G/C πολυμορφισμούς[122,124]. Συνεπώς, τα επίπεδα του μη συνδεδεμένου με την ΙΙ.…”
unclassified